Analisis Resepsi Sastra pada Drama Monolog Prodo Imitatio Karya Arthur S. Nalan - Dea Permataningtyas; Rita Ferina; Joko Purwanto (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to describe the literary reception analysis of the monologue drama “Prodo Imitatito” by Arthur S. Nalan using a literary reception approach. Literary reception is a literary genre that examines literary texts by considering the reader as the giver of the response. This research refers to the understanding and assessment given by the audience to literary works. The method used in this research is descriptive qualitative method, which describes and describes the subject or object of a study that raises the facts found in the research studied. The data in this study are the answers (receptions) of the audience contained in the questionnaire list. The data source in this research is the questions contained in the research questionnaire. Informants/subjects of research are all individuals who are the source of data collection, in this case, students of the Indonesian Language and Literature Education Study Program at Muhammadiyah Purworejo University. The monologue “Prodo Imitatio” tells the story of a middle-aged man who has been spoiled and lazy to study since childhood. After failing to get a bachelor's degree, he is ashamed and ends up running a business of buying and selling fake degrees at the fictitious institution “University of Zuzulapan” to fulfill his social ambitions. The results showed that this literary reception study succeeded in bringing the audience and readers into the storyline.